Current and Future Status of Chemistry Collections and Chemistry Libraries at ARL Institutions. - Jeremy R. Garritano (Issues in Science and Technology Librarianship)
The process of consolidating science and technology branch libraries in academic institutions is not new, but with ease of access to electronic resources, and with shrinking budgets and interdisciplinary research the norm, the idea of consolidation has become more attractive in the past decade. This article reports on the results of a 2005 survey of Association of Research Libraries (ARL) institutions and the status of their chemistry-related library resources and facilities. The past, present, and future of these chemistry collections will be discussed with emphasis on those having consolidated in the last ten years or those who plan to consolidate in the next ten years. Funding sources, characteristics of the physical facilities, and reasons for consolidation are discussed. [ABSTRACT FROM AUTHOR]